Disfagia pasca kemoradiasi pada karsinoma nasofaring - Mayangsari, Ika Dewi; Rachmawati, Elvie Zulka Kautzia; Az Zahra, Amira (Oto Rhino Laryngologica Indonesiana, 2024)
Background: Dysphagia is one of the early and long-term consequences of nasopharyngeal carcinomamanagement. Chemotherapy with radiation may improve the local control and survival rate but also canlead to serious dysphagia caused by radiation damage, and chronic alteration of tissues leading to fibrosisthat can happen during or soon after the radiation therapy. Dysphagia can result in dehydration andmalnutrition, place people at risk of aspiration, and reduce the quality of life by increasing anxiety anddepression. Purpose: Identifying causes, relevant factors, clinical presentation, and management of postchemoradiation dysphagia in nasopharyngeal cancer patients. Literature review: Structures demonstratingpost-therapy changes were deemed as dysphagia aspiration-related structures (DARS). Management ofnasopharyngeal carcinoma is radiotherapy with fibrosis found in 38.2% of the nasopharyngeal carcinomapatients on at least one side of the neck post-treatment. The presence of fibrosis in the pharyngeal andlaryngeal muscles impacted hyoid bone anterior movement and upper esophageal sphincter relaxationcontributed to dysphagia. Fiberoptic Endoscopic Evaluation of Swallowing (FEES) is utilised to detectdysphagia in these patients. The treatment algorithm for dysphagia after chemoradiation consists of historytaking, clinical evaluation, instrumental examination, and management. The management options may bebehavioral, medical, surgical, or combination. Conclusion: Identifying the cause, the components of thedeficit, and the relevant patient factors has prime importance in managing dysphagia besides consideringthe options and weighing the risks versus benefits.   Keywords: Dysphagia, chemoradiation, nasopharyngeal carcinoma, dysphagia aspiration-related structures, fiberoptic endoscopic evaluation of swallowing